Bureaucratic Innovation in the Smart City Era: An Analysis of the Implementation of the Electronic Based Government System (SPBE) - Fahmi, Ade; Perdanaputra, Decky; Komaria, Siti (JURNAL SOSIAL DAN HUMANIS SAINS, 2021)
This study explores the implementation of the Electronic-Based Government System (SPBE) as a form of bureaucratic innovation in the context of smart city development in Indonesia. Using a qualitative descriptive method, the research was conducted in three local governments selected based on their engagement with SPBE initiatives and urban governance programs. Data were collected through in-depth interviews, document analysis, and direct observation to examine how SPBE is institutionalized, integrated, and experienced at the local level. The findings reveal considerable variation in implementation success, influenced by leadership commitment, digital infrastructure, human resource capabilities, and inter-agency coordination. While some regions have demonstrated effective innovation in aligning SPBE with smart governance goals, others face persistent challenges such as bureaucratic inertia, lack of digital literacy, and fragmented systems. This study concludes that bureaucratic innovation through SPBE requires not only technological advancement but also cultural, organizational, and regulatory transformation. The research contributes to the discourse on digital government by highlighting the importance of local context, institutional readiness, and strategic leadership in realizing effective smart city governance.